2011
DOI: 10.1029/2011jf002000
|View full text |Cite
|
Sign up to set email alerts
|

Linking the effective thermal conductivity of snow to its shear strength and density

Abstract: [1] The effective thermal conductivity of snow, k eff , is a crucial climatic and environmental variable. Here, we test the intuition that k eff is linked to microstructural and mechanical properties by attempting to relate k eff to density r snow , and to shear strength s measured with a handheld shear vane. We performed 106 combined measurements of k eff , r snow and s in the Alps, Svalbard, Arctic Alaska, and near the North Pole, covering essentially all snow types. We find a good correlation between k eff … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 29 publications
(118 reference statements)
7
43
1
Order By: Relevance
“…In our modeling study, the thermal conductivity was computed as a function of density following Yen's parameterization (1981). Although the parameterization has proven to be adequate for numerous snowpack conditions, density is not a perfect predictor of snow thermal conductivity, and snow mechanical properties also come into play, with harder snows being more conductive for a given density (Domine et al, 2011a). Here the surface snow at Dome C was very soft, likely implying a lower thermal conductivity than predicted by Yen (1981).…”
Section: Simulated Surface Mass and Energy Balancementioning
confidence: 93%
“…In our modeling study, the thermal conductivity was computed as a function of density following Yen's parameterization (1981). Although the parameterization has proven to be adequate for numerous snowpack conditions, density is not a perfect predictor of snow thermal conductivity, and snow mechanical properties also come into play, with harder snows being more conductive for a given density (Domine et al, 2011a). Here the surface snow at Dome C was very soft, likely implying a lower thermal conductivity than predicted by Yen (1981).…”
Section: Simulated Surface Mass and Energy Balancementioning
confidence: 93%
“…This became evident in temperature gradientsnow metamorphism experiments at a constant density: heat conductivity increased as much as twice its initial value in response to changes in structure and texture (Scheebeli and Sokratov, 2004), showing strong anisotropic behaviour (Shertzer and Adams, 2011). Moreover, Dominé et al (2011) observed that the thermal conductivity of snow can be expressed as a function of snow density and shear strength alone.…”
Section: Heat Conductionmentioning
confidence: 97%
“…To convert the snow reservoir s snow from water equivalents to thickness of snow cover snow in metres, s snow is multiplied by the fraction of density of water and density of snow (Domine et al, 2011):…”
Section: B45 Snow Layermentioning
confidence: 99%
“…For the sake of simplicity, no ranges are specified for these parameters; only average values of the corresponding variables are used. The density of snow, for instance, varies typically from 100-500 kg m −3 (Domine et al, 2011), depending on many factors, such as…”
mentioning
confidence: 99%